Production and characterization of chitosan fibers and 3-D fiber mesh scaffolds for tissue engineering applicattions - Tuzlakoglu, K. (2004)
This study reports on the production of chitosan fibers and 3-D fiber meshes for the use as tissue engineering scaffolds. Both structures were produced by means of a wet spinning technique. Maximum strain at break and tensile strength of the developed fibers were found to be 8.5% and 204.9 MPa, respectively. After 14 d of immersion in simulated body fluid (SBF), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), and inductively coupled plasma emission (ICP) spectroscopy analyses showed that a bioactive Ca-P layer was formed on the surface of the fibers, meaning that they exhibit a bioactive behavior. The samples showed around 120% max. swelling in physiological conditions. The pore sizes of 3-D chitosan fiber mesh scaffolds were observed to be in the range of 100-500 m by SEM. The equilibrium-swelling ratio of the developed scaffolds was found to be around 170% (w/w) in NaCl solution at 37 °C. Besides that, the limit swelling strain was less than 30%, as obtained by mechanical spectroscopy measurements in the same conditions. The viscoelastic properties of the scaffolds were also evaluated by both creep and dynamic mechanical tests. By means of using short-term MEM extraction test, both types of structures (fibers and scaffolds) were found to be non-cytotoxic to fibroblasts. Furthermore, osteoblasts directly cultured over chitosan fiber mesh scaffolds presented good morphology and no inhibition of cell proliferation could be observed.